Low recognition of attention deficit hyperactivity disorder in adult patients admitted to the Epilepsy Monitoring Unit. Issue 8 (27th July 2022) - Pham, Caitlynn; Roy, Cayla; Tang, Christine; Maheshwari, Atul
Abstract: Introduction: Adult patients with epilepsy (PWE) have an 18% prevalence of comorbid attention deficit hyperactivity disorder (ADHD) compared to a prevalence of 2%–5% in the general population. Recognition of this dual diagnosis is important since stimulant therapy is both safe and effective in this population. Methods: Here, we aim to determine if PWE have adequate documentation for comorbid ADHD when being admitted to the Epilepsy Monitoring Unit (EMU). A retrospective review was conducted at the Baylor St. Luke's Medical Center EMU for patients presenting between July 2017 and November 2020. Patients were divided into two groups: Group I—patients without a documented ADHD diagnosis or ADHD medications and Group II—patients with a documented ADHD diagnosis and/or taking medications indicated specifically for ADHD. Results: Of 524 individual patients who presented to the EMU, only 25 patients (4.8%) had documentation of a diagnosis of ADHD and/or ADHD medications (Group II). The proportion of patients in Group II did not significantly differ based on the EMU diagnosis. However, there was a significantly greater number of other psychiatric diagnoses ( p = .005) and a greater number of psychiatric medications prescribed ( p < .001) in patients in Group II. Conclusion: Our study suggests that ADHD is underrecognized and underdiagnosed in patients presenting to the EMU, and screening tools may be useful to help clinicians address seizure comorbidities such as ADHD. Graphical Abstract: